2021
DOI: 10.7454/jki.v24i2.1306
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Factors in Stunting Among Vulnerable Children

Abstract: Children with stunting in Indonesia and other low-middle countries remains a serious problem. This study aimed to identify the association between maternal education, maternal age, maternal height, preceding birth interval, and ANC clinic visits and stunting among vulnerable children in Kupang Regency, Indonesia. A cross-sectional study was conducted of two villages in Kupang Regency. The study sample comprised female ex-refugees from Timor Leste who had children aged 24–59 months. The subjects were chosen usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Father's education is associated with stunting, but mother's education is more strongly associated with stunting 28 . Children have 2 times higher risk of stunting The proportion of lower mothers is higher than that of highly educated mothers 29 .…”
Section: Discussionmentioning
confidence: 90%
“…Father's education is associated with stunting, but mother's education is more strongly associated with stunting 28 . Children have 2 times higher risk of stunting The proportion of lower mothers is higher than that of highly educated mothers 29 .…”
Section: Discussionmentioning
confidence: 90%
“…The second most common country was India ( n = 18 studies) (Ansuya et al, 2018 ; Ashok et al, 2015 ; Basit, 2012 ; Bharathi, 2021 ; Chungkham et al, 2020 ; Gupta & Santhya, 2020 ; Ishwarji et al, 2018 ; Khan & Raza, 2016 ; Patel et al, 2021 ; Rachana et al, 2020 ; Rajaram et al, 2003 ; Rana et al, 2021 ; Sengupta et al, 2010 ; Singh et al, 2017 ; Sk et al, 2021 ; Som et al, 2006 , 2007 ; Yadav & Nilima, 2021 ), followed by Nepal ( n = 7 studies) (Adhikari et al, 2017 ; Alelign et al, 2015 ; Dahal et al, 2021 ; Hanley‐Cook et al, 2022 ; Karki et al, 2021 ; Pravana et al, 2017 ; Tiwari et al, 2020 ) (see Supporting Information S1 : Table S6 ). Additionally, 11 studies were conducted in multiple countries (Achakzai & Khan, 2016 ; Angeles‐Agdeppa et al, 2019 ; Farid‐ul‐Hasnain & Sophie, 2010 ; Gribble et al, 2009 ; Ikeda et al, 2013 ; Mendes Kiik & Saleh Nuwa, 2021 ; Naz & Patel, 2020 ; Naz et al, 2020 ; Nojoumi et al, 2004 ; Olita'a et al, 2014 ; Satti & Farooq, 2023 ). Out of the 56 studies, the majority utilised a cross‐sectional design ( n = 50).…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the age of the maternal age at childbirth was not associated with the incidence of stunting. The previous research has also shown no significant relationship between maternal age and the incidence of stunting [31]. The age of the mother at high risk in pregnancy is >20 or <35 years [9], and the relatively young age of the mother is closely related to failure to thrive in infants aged 0-11 months [32].…”
Section: The Relation Between Maternal Age At Childbirth and The Inci...mentioning
confidence: 99%